School restructuring in England: New school configurations and new challenges. (January 2015) - Simkins, Tim
This article considers the ways in which government policy in England is causing local schooling landscapes to be reconfigured. By August 2014, 12 percent of primary schools and 53 percent of secondary schools had become academies – 'independent publicly funded schools' directly responsible to the Secretary of State. The article begins by considering ways in which schools may choose, or be forced, to respond to this policy environment, and, in particular, the new forms of school grouping that may emerge. It then draws on case studies of three local authorities – a large metropolitan authority, a large rural county and a small unitary authority – to explore changing patterns of schooling. It notes that rates of 'academization' vary between the three areas, that local and regional groupings have gained greater purchase than national chains, and that, even allowing for this, almost half the academies are stand-alone – not belonging to any formal grouping. It concludes by arguing that deeper understanding of emerging patterns will require further study of the ways in which the values, purposes and power of key actors interact as decisions are taken about schools' futures.